Integration of face-to-face and virtual classes improves test scores in Biology undergraduate courses on days with flooding in Brazil - doi: 10.4025/actascieduc.v35i1.17219 - Otacílio Antunes Santanta; Talita Pereira Silva; Euzelina dos Santos Borges Inácio; Girlanny Simplicio de Oliveira; Myllena Matias da Silva; Jose Imana Encinas (Universidade Estadual de Maringá, 2012)
Ubiquitous Education, omnipresent education, has established with the using of virtual learning objects, and integrating with the face-to-face classroom brought satisfactory results in the knowledge construction. In parallel, one of the recurring problems of cities is the traffic immobility and consequently the student's arrival to the University. In days of flooding, the student takes longer to get to university or sometimes cannot reach. This work has the hypothesis that the integration of face-to-face classes with virtual classes would be the option for the days of traffic immobility in cities. The objectives of this work were: i) to analyse the types of transport used by students from their homes to go to university, ii) to analyse how long students spent commuting from their homes to university, and iii) compare the results of student evaluations of biology courses that have lessons integrated between virtual and face-to-face classes with students who only have face-to-face classes. Six metropolitan areas of Brazil were evaluated for two semesters, one with flooding days and another without. The results indicated that students who had a virtual support of the discipline, mainly on flooding days, had higher grades and success in knowledge construction.